2012
DOI: 10.1021/nl203649p
|View full text |Cite
|
Sign up to set email alerts
|

MoO3–x Nanowire Arrays As Stable and High-Capacity Anodes for Lithium Ion Batteries

Abstract: In this study, vertical nanowire arrays of MoO(3-x) grown on metallic substrates with diameters of ~90 nm show high-capacity retention of ~630 mAhg(-1) for up to 20 cycles at 50 mAg(-1) current density. Particularly, they exhibit a capacity retention of ~500 mAhg(-1) in the voltage window of 0.7-0.1 V, much higher than the theoretical capacity of graphite. In addition, 10 nm Si-coated MoO(3-x) nanowire arrays have shown a capacity retention of ~780 mAhg(-1), indicating that hybrid materials are the next genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
225
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 278 publications
(233 citation statements)
references
References 20 publications
5
225
0
Order By: Relevance
“…Such behavior has been observed in other anode materials systems. 9,25 The first cycle charging (lithium alloying) has a slope at the region between 0.3-0.002 V. After the first cycle, the charge and discharge profile shows the sloping curves of lithium intercalation with Li x Si. The average charge potential is around ∼0.2 V and discharge potential of ∼0.4 V, suggesting a low average potential of ∼0.1 V, which means silicon nanotube anode is a good electrode with low charge/discharge hysteresis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Such behavior has been observed in other anode materials systems. 9,25 The first cycle charging (lithium alloying) has a slope at the region between 0.3-0.002 V. After the first cycle, the charge and discharge profile shows the sloping curves of lithium intercalation with Li x Si. The average charge potential is around ∼0.2 V and discharge potential of ∼0.4 V, suggesting a low average potential of ∼0.1 V, which means silicon nanotube anode is a good electrode with low charge/discharge hysteresis.…”
Section: Resultsmentioning
confidence: 99%
“…4,5 The improved performance of nanometer size materials is due to the smaller domain size compare to the critical size for the fracture which is estimated to be about 300 nm for Si. 6 Using this hypothesis, several 0-D and 1-D morphologies at nanoscale have been tried; they include nanoparticles, 7 nanowires, 8,9 Si thin films 10,11 and silicon/graphene 12,13 composites. In the case of Si thin films, the main advantage is that they are free from conductive additives and binders which simplify their characterization and use.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This may be because it is difficult to grow MoO 3 nanorods in the vertical direction by simple methods. MoO 3 nanorod arrays have been synthesized by several methods, such as thermal evaporation, [38] pulsed electron beam, [39] RF sputtering, [40] and chemical vapor deposition, [41] all of which are time consuming and require complicated vacuum systems. Recently, Zheng et al [42] reported a two-step solution-based route to synthesize MoO 3 nanorod arrays by firstly depositing a seed layer and subsequent hydrothermal treatment to directly grow well-aligned MoO 3 and MoO 2 nanorods on metallic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these drawbacks, different MoO 3 nanostructures have been prepared for enhancing their electrochemical performance. The preparation of MoO 3 as nanobelts [12], nanorods [13], nanowires [14] and nanosheets [15,16] has been widely investigated. In addition, it has been confirmed that the electrochemical performance is strongly related to the electrical conductivity of the electrodes.…”
Section: Introductionmentioning
confidence: 99%